A hybrid multiple criteria decision making approach for measuring comprehensive performance of reverse logistics enterprises. (September 2018) - Shaik, Mohammed Najeeb; Abdul-Kader, Walid
Highlights: A multi-criteria performance measurement hybrid model to assess the RLE performance. DEMATEL, fuzzy ANP & AHP methods are used for inner & inter dependencies analysis. Model determines the overall comprehensive performance index. Model includes performance attributes & achieves a realistic representation of RLE. Model supports decision makers for improving RLE performance. Abstract: The area of reverse logistics has recently received considerable attention and is an important business policy. The performance measurement of reverse logistics is seldom studied due to the complexity and uncertainty of its operations. This paper provides a multi-criteria performance measurement model to assess the reverse logistics enterprise's performance by considering performance attributes such as product lifecycle stages, strategies, processes, capabilities, and perspectives and measures. In developing the performance measurement model, a hybrid multi-criteria approach combining DEMATEL, fuzzy ANP and AHP methods are applied. Furthermore, the relative importance of these attributes and their criteria with respect to each other and their contribution to the overall performance are affected by the competitive outlook considered by the reverse logistics enterprises. The performance evaluation model developed in this paper incorporates relevant attributes and achieves a more realistic representation of the enterprise's performance by calculating the overall comprehensive performance index. This study provides decision makers a basis for improving the reverse logistics enterprise performance.